An Econometric Estimation and Prediction of the Effects of Nominal Devaluation on Real Devaluation: Does the Marshal-Lerner (M-L) Assumptions Fits in Nigeria? - Rafindadi, Abdulkadir Abdulrashid; Yusof, Zarinah (International Journal of Economics and Financial Issues, 2014)
Nigeria has been depending on oil as its major export commodity for decades leading to the neglect of other vital economic resources. This situation led to massive unemployment as a result of an undiversified economic system, which in turn created an alarming paucity of external accruals to finance the lingering poverty level of the country. Similar to this, several economic indexes and researchers have been pointing out delusive and inconclusive growth attainment of the country which has not impacted positively on the populace. It is against this backdrop that this study aims to re-investigate whether nominal effective exchange rate could lead to real effective exchange rate and if this can be a synergistic strategy towards spurring competitive trading relationship between Nigeria and the rest of the globe. To ensure this, we use a quarterly time series data from 1971QI-2012QVI, and applied the traditional and structural break unit root tests; the Bayer-Hanck cointegration approach and the VECM-Granger causality test. The findings of the study confirmed that nominal effective exchange rate leads to real effective exchange rate and inflation exerts positive impact on real effective exchange rate in Nigeria. In addition, the study found that real effective exchange rate has positive impact on nominal effective exchange rate, but inflation declines it. The causality analysis, on the other hand, revealed that there is feedback effect between real and nominal effective exchange rates, between nominal effective exchange rate and inflation and between inflation and real effective exchange rate. This finding suggests that there are crystal avalanche of competitive opportunities for the country to jettison all its economic vices and move progressively in international trade with minimal hurdles, thus fitting in with the Marshall-Lerner assumption (M-L). Keywords: Marshall-Lerner; devaluation; exchange rates; cointegration JEL Classifications: C2; C5; F1; G0